Pell grants and labor supply: Evidence from a regression kink - Michael S. Kofoed (W.E. Upjohn Institute for Employment Research, 2022)
A concern in higher education policy is that students are taking longer to graduate. One possible reason for this observation is an increase in off-campus labor market participation among college students. Financial aid may play a role in the labor/study choice of college students-as college becomes more affordable, students my substitute away from work and toward increased study. I use data from the National Postsecondary Student Aid Study (NPSAS) to exploit nonlinearity in the Pell Grant formula to estimate a regression kink and regression discontinuity designs. I find that conditional on receiving the minimum of 550, students reduce their labor supply by 0.4 hours per week, which translates to a 2.4 percent decrease in hours worked. Students who receive the average Pell Grant of 2,250 are 7.6 percentage points (or around 12 percent) less likely to work and, if working, supply 5.10 less hours per week, or around 30.67 percent reduction. I find Pell Grants do increase academic achievement, implying that students substitute study time for work.
Keywords: I22; I23; J20; 330; Pell Grants; financial aid; regression kink; labor supply